Proton Image-guided Radiation Assignment for Therapeutic Escalation via Selection of locally advanced head and neck cancer patients [PIRATES]: A Phase I safety and feasibility trial of MRI-guided adaptive particle radiotherapy. (January 2022) - van Dijk, Lisanne V.; Frank, Steven J.; Yuan, Ying; Gunn, Brandon; Moreno, Amy C.; Mohamed, Abdallah S.R.; Preston, Kathryn E.; Qing, Yun; Spiotto, Michael T.; Morrison, William H.; Lee, Anna; Phan, Jack; et al.
Highlights: The PIRATES protocol is a novel tumor radiation dose-escalation approach. PIRATES integrates proton therapy, image guided RT and hybrid hyper-fractionation. It targets only head and neck cancer patients at high risk of treatment failure. This Phase I trial aims to test the feasibility and safety of PIRATES. Abstract: Introduction: Radiation dose-escalation for head and neck cancer (HNC) patients aiming to improve cure rates is challenging due to the increased risk of unacceptable treatment-induced toxicities. With "Proton Image-guided Radiation Assignment for Therapeutic Escalation via Selection of locally advanced head and neck cancer patients" (PIRATES), we present a novel treatment approach that is designed to facilitate dose-escalation while minimizing the risk of dose-limiting toxicities for locally advanced HPV-negative HNC patients. The aim of this Phase I trial is to assess the safety & feasibility of PIRATES approach. Methods: The PIRATES protocol employs a multi-faceted dose-escalation approach to minimize the risk of dose-limiting toxicities (DLTs): 1) sparing surrounding normal tissue from extraneous dose with intensity-modulated proton therapy, 2) mid-treatment hybrid hyper-fractionation for radiobiologic normal tissue sparing; 3) Magnetic Resonance Imaging (MRI) guided mid-treatment boost volume adaptation, and 4) iso-effective restricted organ-at-risk dosing to mucosa and bone tissues. The time-to-event Bayesian optimal interval (TITE-BOIN) design is employed to address the challenge of the long DLT window of 6 months and find the maximum tolerated dose. The primary endpoint is unacceptable radiation-induced toxicities (Grade 4, mucositis, dermatitis, or Grade 3 myelopathy, osteoradionecrosis) occurring within 6 months following radiotherapy. The second endpoint is any grade 3 toxicity occurring in 3–6 months after radiation. Discussion: The PIRATES dose-escalation approach is designed to provide a safe avenue to intensify local treatment for HNC patients for whom therapy with conventional radiation dose levels is likely to fail. PIRATES aims to minimize the radiation damage to the tissue surrounding the tumor volume with the combination of proton therapy and adaptive radiotherapy and within the high dose tumor volume with hybrid hyper-fractionation and not boosting mucosal and bone tissues. Ultimately, if successful, PIRATES has the potential to safety increase local control rates in HNC patients with high loco-regional failure risk. Trial registration: ClinicalTrials.gov ID: NCT04870840; Registration date: May 4, 2021. Netherlands Trial Register ID: NL9603; Registration date: July 15, 2021.